Endoscopic submucosal dissection (ESD) for Barrett’s esophagus (BE)-related early neoplasia after standard endoscopic management is feasible and safe - Tomizawa, Yutaka (Endosc Int Open, 2020)
Background and study aims  There is little data on the feasibility and safety of endoscopic submucosal dissection (ESD) as a salvage treatment for Barrett’s esophagus (BE)-related neoplasia after standard endoscopic treatments. Patients and methods  A multicenter retrospective analysis on patients who underwent ESD for BE was performed. The primary endpoint was effectiveness of obtaining en-bloc resection in salvage as compared to non-salvage treatments. Results  Median age was 71 (IQR 55 – 79) years. Twelve (37%) of 32 patients underwent salvage ESD. Median resection time was 100 (IQR 60 – 136) minutes. En-bloc resection was achieved in 31 patients (97 %). Complete R0 resection was obtained in 75 % in the salvage group and 80 % in the non-salvage group ( P  = 1.00). In seven patients (22 %), the pre-ESD diagnosis was upgraded on post-ESD histopathology (1 low-grade dysplasia to high grade dysplasia [HGD], 4 HGD to early esophageal carcinoma (EAC), and 2 intramucosal EAC to invasive EAC). No perforations occurred in either group. Two late adverse events occurred, both in the salvage group ( P  = 0.133). Delayed bleeding occurred in a patient who had just resumed warfarin and stricture occurred in a patient who had a circumferential resection requiring serial dilation and stent placement. Conclusions  Our cohort study demonstrated that ESD as salvage therapy for BE related neoplasia is feasible and safe, achieving similar high rates of en-bloc resection and complete R0 resection as in treatment-naïve patients. Referral to an expert center performing ESD should be considered for patients with recurrence or progression following endoscopic mucosal resection or ablation therapy.